Taste Perception from Jamu Drinks Color for Younger Generation by using Photo Products - Andreas Kurniawan; Yasraf Amir Piliang; Agung Eko Budiwaspada (International Journal of Management, Entrepreneurship, Social Science and Humanities, 2023)
Jamu is a traditional herbal drink from Indonesia that has been inherited from generation to generation. Jamu drinks have a variety of recipes since their ingredients are derived from a combination of typical Indonesian spices that can be obtained in local markets. Previously, jamu was frequently associated with a bitter taste, but due to improvements and innovations, it may now adapt to the preferences of the younger generation. Moreover, modification of a recipe's look involving different hues may cause consumers to speculate about its taste. This study examines taste perception from the Indonesian traditional herbal drinks "jamu" color for the younger generation by using photo products image. The research method was conducted through experimentation by using a questionnaire and forum discussion in 2 phases on 111 visual communication students with an average age of 21.7 years. Results: white, red, blue, and yellow colors were preferred by the majority of participants, followed by orange and brownish-red colors, which were still mostly acceptable. However, brown and green were perceived as the colors that participants disliked the most. Based on the result of this experiment, it can be concluded that human perception of color and taste can also be applied to traditional herbal medicine; this result supports the innovative exploration of jamu recipes that can adapt to the tastes of the younger generation. The result of this study shows that perception is influenced by previous experience; several times, the data showed significantly that colors such as milk or common fruit juice would be perceived the same as the taste of jamu. Furthermore, these findings strengthen various previous studies that the color will be able to make humans perceive its taste; although sometimes the perception is wrong, it can be used as an important reference for industries. In addition, the results of this study also show that the perception of color can be done without the need to see the product directly.